Children's cognitive abilities in construction and programming robots - Caci, B.; D'Amico, A. (IEEE International Workshop on Robot and Human Interactive Communication 2002, 2002)
The aim of the present pilot study, that involved a group of eleven-years-old Italian subjects, is to study the relationship between non-verbal intelligence, visual-constructive ability, logical reasoning, and the abilities in construction and behavioral programming of LEGO Mindstorm Robots. As expected, results showed that children with high level in the cognitive tests are more able titan others both in the robot body construction and in the robot behavioral programming. Implications for future research are emphasized.